Bouwen aan morgen met het bouwmateriaal van gisteren: Tobit 7-8 over de rol van geliefeden als hoeders en verzorgers van elkanders psychische kwitsuren* - Veulemans, S. (Faculty of Theology, University of the Free State, 2008)
English: A painful past can spoil a person’s perspective on the future, which, in the case of a couple, can put pressure on their future together. For these people, as well as for all those who tackle this problematic in their research, the Tobit novella can provide some significant and fundamental insights. Sarah’s mysterious affliction, which symbolises all possible af flictions, is an unwelcome part of the couple’s relationship. Tobias, however, understands that loving one another implies not only that one is called to care about, be dedicated to, and take responsibility for one’s own behaviour, but also that one is subject to an appeal made by events from the other’s past, even if one was oneself not involved in these events. He realises that it will only be possible to share a future together if the chaos of Sarah’s past can be transformed, which begins when Tobias kills the voracious fish in the Tigris River, a symbolic representation of destructive chaos. Once this has been defeated, Tobias is also able to triumph over Asmodeus, the demon responsible for the misfortune Sarah has had in her relationships and who also personifies the dark forces of chaos. This adventure story gives metaphorical expression to the idea that partners can descend with each other into the chaos of the past in order to bring about a new order, through which the future is made possible. In this way, “to love” becomes synonymous with the generation of a future in which the ideal of Paradise is brought ever closer.
Keywords: Tobit; Relationships; Narrative reading of the Bible; Psychological fragility